Reformasi Birokrasi Dalam Rangka Meningkatkan Potensi dan Kompetensi Aparatur Pemerintah Daerah Guna Terwujudnya Good Governance - Rahma Agnia Fauziah; Hanny Purnamasari; Gun Gun Gumilar (Peneliti.net, 2022)
In carrying out bureaucratic reform, of course, it is necessary to have potential and competent government officials which are expected, with their presence, to create good governance. And, for the realization of all this, principles, principles and strategies must be applied by the government apparatus. Meanwhile, in reorganizing a bureaucracy, there are several models among which there are 3 (three) models, namely strengthening government regulations and policies, implementing e-government and e-governance, and collaborative governance.